Type and Duration of Dual Antiplatelet Therapy in Complex Percutaneous Coronary Intervention - Dimitrios Alexopoulos; Charalampos Varlamos; Despoina-Rafailia Benetou (US Cardiology Review, 2020)
Complex percutaneous coronary intervention (PCI) patients are a high-risk population for ischemic complications. Antiplatelet therapy in such patients remains controversial, as the beneficial effects of more potent agents use or prolonged dual antiplatelet treatment (DAPT) on atherothrombotic complications are hindered by a concomitant increase in bleeding rates. The aim of this article is to describe ischemic and bleeding outcomes associated with complex PCI procedures and to compare different types and durations of DAPT regimens in terms of safety and efficacy outcomes. Issues concerning special patient groups, such as those with left main, chronic total occlusion, or bifurcation lesions, are discussed.